Transparent wood preparation method based on wood xerogel and product application thereof
Through the transparent wood preparation method based on wood xygel, the problems of complex chemical treatment and performance balance in the prior art are solved, and the preparation of high-performance transparent wood composite materials is realized, which is suitable for high-performance applications in many fields.
Patent Information
- Application Number
- CN202411938692.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-26
- Publication Date
- 2025-03-25
AI Technical Summary
The existing transparent wood preparation technology has complex chemical treatment processes, which increases environmental pollution and production costs, while it is difficult to achieve an ideal balance between mechanical properties and optical transparency.
A transparent wood preparation method based on wood xygel is adopted, and a high specific surface area and high mesoporous volume of wood xygel is prepared through steps such as delignin treatment, TEMPO oxidation treatment, solvent exchange and aluminum ion crosslinking, and photocuring reaction with acrylic resin to form a high-performance transparent wood composite material.
It achieves high porosity, specific surface area and excellent mechanical properties, while maintaining high optical transparency, and is suitable for high performance applications in the fields of architecture, optoelectronics and energy.
Smart Images

Figure CN119682010A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of wood xerogels, and in particular relates to a method for preparing transparent wood based on wood xerogels and product application thereof. Background Art
[0002] With the improvement of global environmental protection awareness and the advancement of sustainable development strategies, the demand for new green building materials is growing. In this context, transparent wood, as a revolutionary sustainable material, has attracted widespread attention from the scientific and industrial communities due to its unique optical and mechanical properties, as well as its renewable and biodegradable characteristics. Transparent wood is prepared by structure-retaining delignification treatment and subsequent infiltration of thermosetting or light-curing polymer resins. It combines the natural beauty of wood with the optical transparency of polymers, providing new material options for the fields of construction, optoelectronics and energy. With the continuous development of transparent wood technology, its application prospects in the future construction and optoelectronics fields are broad. For example, with the increasing requirements of energy conservation and environmental protection in the construction industry, transparent wood, as a new building material, has a growing market demand. In the field of construction, transparent wood can be used to manufacture energy-saving windows that can not only effectively transmit light but also provide good thermal insulation, thereby reducing the energy consumption of buildings. In the field of optoelectronics, the high optical transparency and good mechanical properties of transparent wood make it an ideal material for the manufacture of solar panels. In addition, transparent wood can also be used to manufacture optical devices, display screens and lighting equipment. Related research fields are exploring more innovative methods to improve the performance of transparent wood, such as modifying wood cell walls through nanotechnology to further improve its optical transparency and mechanical properties. In addition, the large-scale production and application of transparent wood are also advancing, and it is expected that transparent wood will occupy an important position in the market in the next few years.
[0003] The preparation and application of transparent wood have positive impacts on both the environment and the economy. From an environmental perspective, the production process of transparent wood uses fewer chemicals, which reduces pollution to the environment. In addition, the biodegradability of transparent wood allows it to decompose naturally at the end of its service life, reducing the problem of waste disposal. From an economic perspective, transparent wood has a low production cost, and its high-performance characteristics enable its application in the construction and photovoltaic fields to improve energy efficiency and reduce long-term operating costs. Despite the many advantages of transparent wood, there are some limitations in existing preparation technologies. Traditional preparation methods usually involve complex chemical treatment processes, such as delignification using harmful chemicals, which not only burdens the environment but also increases production costs. In addition, existing transparent wood often has difficulty in achieving an ideal balance between mechanical properties and optical transparency, limiting its use in high-performance applications. In terms of optical properties, the low mesoporous volume of wood cell walls leads to insufficient penetration of polymer resins, affecting the optical transparency of the final product. In addition, the optical transparency of existing transparent wood tends to decrease significantly when the thickness increases, which limits its use in applications that require thicker materials, such as architectural windows and solar panels. In order to solve the limitations of existing transparent wood preparation technology, the present invention proposes a transparent wood preparation method based on wood xerogel technology. Wood xerogel is a material with high specific surface area and high mesoporous volume, which can be prepared by evaporative drying of delignified wood. This high mesoporous volume wood xerogel allows the penetration of resin monomers without solvents at room temperature, thereby preparing high-performance transparent wood composite materials.
[0004] The advantage of wood xerogel technology lies in its high specific surface area and high mesopore volume, which allows the polymer resin to fully penetrate into the wood cell wall, thereby improving the optical transparency of transparent wood. In addition, the compressible properties of wood xerogel make it compressible in the lateral direction, which makes it possible to precisely control the microstructure, wood volume fraction and mechanical properties of transparent wood composites without affecting their optical transmittance. In this way, large-sized, high-wood volume fraction (50%) transparent wood composites can be successfully prepared, demonstrating the potential scalability of this method. However, in the current processing methods related to wood xerogel, there is a situation where the mechanical properties and adsorption properties of the obtained products cannot be achieved at the same time, and other properties such as transmittance and haze are not ideal. In short, in order to prepare a transparent wood with wood xerogel that has all the properties, it is still necessary to gradually optimize. Summary of the invention
[0005] The purpose of the present invention is to overcome the defects of the above-mentioned prior art and provide a transparent wood of wood xerogel with high porosity and large specific surface area and excellent mechanical properties. The wood preparation method is simple and environmentally friendly, and can meet the high-performance application requirements in the fields of construction, optoelectronics and energy.
[0006] In summary, transparent wood, as a new type of sustainable building material, has important research value and application prospects. The transparent wood preparation method based on wood dry gel technology proposed in the present invention not only overcomes the limitations of the existing technology, but also provides new possibilities for the large-scale production and application of transparent wood. With the continuous advancement of transparent wood technology, its application in the fields of construction, optoelectronics and energy will become more and more extensive, contributing to the realization of sustainable development goals.
[0007] An object of the present invention is to provide a method for preparing transparent wood based on wood xerogel, which comprises the following steps:
[0008] S1, delignifying the wood to obtain pretreated wood;
[0009] S2, oxidizing the pretreated wood with TEMPO to obtain an intermediate product;
[0010] S3, exchanging the solvent of the intermediate product and converting it into a wood xerogel, and cross-linking it with aluminum ions to obtain a precursor;
[0011] S4, subjecting the precursor to a photocuring reaction with an acrylic resin to obtain a crude product;
[0012] S5. Compressing the crude product to obtain a product.
[0013] Furthermore, the method for preparing transparent wood based on wood xerogel, wherein:
[0014] The density of the wood is 150-400 kg / m 3 ; and cutting the wood.
[0015] Furthermore, the method for preparing transparent wood based on wood xerogel, wherein:
[0016] In the step S3, the step of cross-linking the aluminum ions is to soak the wood xerogel in aluminum ion solutions of different concentrations in batches.
[0017] Ionic crosslinking strengthens the connection between cellulose microfibrils in wood cell walls by forming metal-carboxylate bridges, thereby improving the mechanical strength and durability of the material.
[0018] Furthermore, the method for preparing transparent wood based on wood xerogel, wherein:
[0019] In the step S3, the concentration of the aluminum ion solution 1 is 0.1-0.5M, and the immersion time is 1-3h; the concentration of the aluminum ion solution 2 is 0.01-0.05M, and the immersion time is 10-48h.
[0020] The purpose of the above operation is to fully ensure the degree of ion exchange. The high concentration and short time immersion at the beginning is to quickly provide a relatively high concentration environment of aluminum ions in the solution; the low concentration and long time immersion is then used to fully ensure the completion of ionic cross-linking.
[0021] The theoretical basis is that the initial high-concentration, short-time immersion will allow a certain amount of aluminum ions to enter the cross-linking network, which is equivalent to being consumed, while the time period for completely completing the ionic cross-linking is relatively long. The subsequent low-concentration, long-time immersion is to ensure that the solution concentration of aluminum ions is within a reasonable range within the relatively long cross-linking completion time.
[0022] On the contrary, if the above operating principles are violated, the results will be unsatisfactory.
[0023] Furthermore, the method for preparing transparent wood based on wood xerogel, wherein:
[0024] In the step S4, in the photocuring reaction, the precursor is mixed with acrylic resin and photoinitiator, placed in the dark overnight, and then photocured.
[0025] Furthermore, the method for preparing transparent wood based on wood xerogel, wherein:
[0026] In the step S5, the compressive strain value is 30-90%.
[0027] Furthermore, in the method for preparing transparent wood based on wood xerogel, the wood is selected from balsa wood.
[0028] Preferably, in the TEMPO-mediated oxidation treatment, the delignified wood is treated by a TEMPO (2,2,6,6-tetramethylpiperidin-1-oxyl free radical)-mediated oxidation method to increase the mesoporous volume and specific surface area of the wood cell wall, thereby improving its adsorption capacity for the polymer resin. This treatment step enhances the interaction between the wood and the resin by introducing functional groups such as carboxyl and hydroxyl groups into the wood cell wall, thereby improving the overall performance of the composite material.
[0029] Preferably, in the preparation of the wood xerogel, the oxidized wood is converted into the wood xerogel by evaporative drying, and the xerogel has a high specific surface area (260 m 2 g–1 ) and high mesoporous volume (0.37 cm 3 g –1 ) and maintain the cell wall structure of the wood. The evaporative drying process is carried out at normal pressure, avoiding the use of harmful solvents and meeting environmental protection requirements. Specifically, the intermediate product is first soaked in 100mL of anhydrous ethanol for two days, and then soaked in 99.5% hexane for two days, and the solvent is changed every 24 hours. The hexane-exchanged wood sample is sandwiched between two layers of polytetrafluoroethylene (PTFE) membranes, placed in a crystallization tank containing 100mL of hexane, and dried at 60°C for 48h in a sealed desiccator together with 500g of silica gel.
[0030] Preferably, during the preparation of ion crosslinking enhancement, the Al 3+ The success of ionic crosslinking was observed in the non-crosslinked wood sample at 1730 cm – 1 The carboxyl absorption peak at 100% disappeared. By mechanical testing, the wood samples before and after crosslinking were compared, and the crosslinked samples showed significantly improved tensile strength (4.81 MPa), Young's modulus (0.32 GPa) and fracture strain (3.62%).
[0031] Preferably, during the resin infiltration and curing, the wood xerogel and the UV-curable acrylic resin (such as ethoxylated bisphenol A diacrylate, ABPE-10) are solvent-free infiltrated at room temperature to achieve uniform distribution of the resin in the wood cell wall. Subsequently, the infiltrated wood xerogel and the resin are treated with UV curing to form a high-performance transparent wood composite material.
[0032] Preferably, during the compression of the crude product, the wood volume fraction of the transparent wood composite material is adjusted by controlling the compression strain (e.g., 30%, 50%, 80%) to achieve different optical and mechanical properties. The cross-sectional microstructure of the compressed wood xerogel was observed using a field emission scanning electron microscope (FE-SEM). The mechanical properties of the composite material were evaluated by tensile and compression tests, and the total light transmittance and haze were measured using a spectrophotometer.
[0033] Another object of the present invention is to provide the use of the transparent wood of the wood xerogel prepared by the transparent wood preparation method of the wood xerogel in building materials.
[0034] The beneficial effects of the present invention are:
[0035] 1. The present invention synergistically improves the mechanical properties, porosity, specific surface area, optical properties and haze of the transparent wood of the wood dry gel through the organic combination of various process sections, so that the product has excellent characteristics and has no performance shortcomings. Specifically, the transparent wood composite material of the present invention has the characteristics of low density, high mechanical properties and low thermal conductivity. The low density property makes the material light and easy to transport and install; the high mechanical properties ensure the strength and durability of the material, and can withstand use under various environmental conditions; the low thermal conductivity provides good thermal insulation performance, which helps to save energy and improve comfort. These characteristics make the transparent wood composite material have a wide range of application potentials in the construction field (such as energy-saving windows, skylights, exterior walls, etc.), the photovoltaic field (such as solar panels, optical devices, display screens, etc.) and the energy field (such as energy-saving building materials).
[0036] 2. The present invention provides an environmentally friendly and cost-effective method for preparing transparent wood, which reduces the use of harmful chemicals and meets the requirements of sustainable development. The prepared transparent wood composite material has excellent optical and mechanical properties and can meet the high-performance application requirements in the fields of architecture, optoelectronics and energy. The method of the present invention has good scalability and is suitable for large-scale production, which helps to promote the widespread application of transparent wood in the market.
[0037] 3. The method of the present invention is not only feasible on a laboratory scale, but also has good potential for large-scale production. By optimizing the parameters of each step, such as the conditions of delignification treatment, the intensity of TEMPO-mediated oxidation treatment, the temperature and time of evaporation drying, the concentration and time of ionic crosslinking, the process of resin penetration and curing, etc., high-efficiency and low-cost production can be achieved. In addition, the method of the present invention uses environmentally friendly materials and solvent-free processes, which meets the current requirements for sustainable production and environmental protection, and helps to reduce the environmental impact during the production process. BRIEF DESCRIPTION OF THE DRAWINGS
[0038] Figure 1 (a) is a comparison diagram of the cell wall structures in Example 1 and Comparative Example 1; Figure 1 (b) is a comparison diagram of isothermal adsorption-desorption curves in Example 1 and Comparative Example 1; Figure 1 (c) is a comparison diagram of the porosity in Example 1 and Comparative Example 1;
[0039] Figure 2 is a transparency comparison diagram of Example 1 and Comparative Example 1;
[0040] Figure 3 is a diagram of large-scale sample preparation in Example 1;
[0041] Figure 4 (a) is a Young's modulus diagram of Example 1; Figure 4(b) is a transmittance diagram of the embodiment at 550 nm;
[0042] Figure 5 (a) is a transmittance comparison diagram of Example 1, Comparative Example 1 and Blank Example; Figure 5 (b) is a haze comparison diagram of Example 1, Comparative Example 1 and Blank Example;
[0043] Figure 6 (a) is a tensile strength test diagram of Example 1 and Comparative Example 2; Figure 6 (b) is a comparison chart of the tensile strength values of Example 1 and Comparative Example 2. DETAILED DESCRIPTION
[0044] In order to more clearly illustrate the technical solution of the present invention, the following examples are listed. Unless otherwise stated, the raw materials, reactions and post-treatment methods shown in the examples are common raw materials on the market and technical methods well known to those skilled in the art.
[0045] Example 1
[0046] A method for preparing transparent wood based on wood xerogel comprises the following steps:
[0047] S1, the density is 350kg / m 3 Balsa wood is subjected to delignification treatment with an acidic sodium chlorate solution to obtain pretreated wood;
[0048] S2, oxidizing the pretreated wood with TEMPO, the steps are: soaking the dried pretreated wood (1 g) in 100 mL of sodium phosphate buffer (pH=6.8), the buffer containing 0.032 g of TEMPO and 2.26 g of NaClO2. Adding 20 mL of 0.1 M NaClO solution to the above solution, and continuing the reaction at 60°C for 48 hours. Finally, an intermediate product is obtained;
[0049] S3, converting the intermediate product into a wood xerogel, the steps are: subjecting the intermediate product to solvent exchange, first soaking it in 100 mL of anhydrous ethanol for two days, then soaking it in 99.5% hexane for two days, and changing the solvent every 24 hours. The wood sample after hexane exchange is sandwiched between two layers of polytetrafluoroethylene (PTFE) membranes, placed in a crystallization tank containing 100 mL of hexane, and dried at 60° C. for 48 hours in a sealed desiccator together with 500 g of silica gel.
[0050] Then, aluminum ions were used for crosslinking, and the specific steps were as follows: the wood xerogel was washed with deionized water, and immersed in a 0.1 M AlCl3 solution for 1 h, and then immersed in a 0.01 M AlCl3 solution for 24 h for ion crosslinking to obtain a precursor;
[0051] S4, photocuring and crosslinking the precursor with acrylic resin, the specific steps are: in a glass culture dish, immerse the wood dry gel in ABPE-10 monomer, add 1wt% of the reaction substrate as photoinitiator 2,2-dimethoxy-2-phenylethanone, and place it in the dark at room temperature overnight for full penetration. The infiltrated wood dry gel is sandwiched between borosilicate glass plates and cured with a 365nm UV lamp for 15 minutes to obtain a crude product;
[0052] S5, compressing the crude product to obtain a product. The specific steps are: using a compressor, applying pressure in a direction perpendicular to the growth direction of the wood, the thickness of the treated wood xerogel is 2.5 cm, the compression amounts are 0.75 cm, 1.25 cm, and 2 cm, and the corresponding material compression strain ratios are 30%, 50%, and 80%, respectively.
[0053] In this embodiment, the compression strain ratio of the final product is controlled at 50%.
[0054] Example 2
[0055] The steps of Example 2 are the same as those of Example 1, with the only difference being that in S3, aluminum ions are cross-linked. The specific steps are as follows: the wood dry gel is washed with deionized water and immersed in a 0.5 M AlCl3 solution for 1 h, and then immersed in a 0.05 M AlCl3 solution for 24 h for ion cross-linking to obtain a precursor.
[0056] Example 3
[0057] The steps of Example 2 are the same as those of Example 1, with the only difference being that in S3, aluminum ions are cross-linked. The specific steps are as follows: the wood dry gel is washed with deionized water and immersed in a 0.25 M AlCl3 solution for 1 h, and then immersed in a 0.25 M AlCl3 solution for 24 h for ion cross-linking to obtain a precursor.
[0058] Comparative Example 1
[0059] The steps of Control Example 1 are the same as those of Example 1, except that in S1, no delignification treatment with an acidic sodium chlorate solution is performed.
[0060] Comparative Example 2
[0061] The steps of Control Example 2 are the same as those of Example 1, except that the S3 step is not included, and the intermediate product is directly subjected to the S4 step.
[0062] Comparative Example 3
[0063] The steps of Control Example 3 are the same as those of Example 1, with the only difference being that in step S3, instead of two-stage AlCl3 solution immersion, the precursor is obtained by directly immersing in 0.01 M AlCl3 solution for 24 h for ionic crosslinking.
[0064] Blank example
[0065] The blank case is a control group without the assistance of wood-based aerogel, that is, the UV-curable acrylic resin (ABPE-10) is directly used in the untreated original wood (Natural wood).
[0066] Test Case
[0067] The performance of Example 1 and Comparative Examples 1-4 was characterized. The following findings were made:
[0068] The product has high porosity (88%) and high specific surface area ( Figure 1 (a) and Figure 1 (b)), providing good conditions for subsequent resin penetration. Afterwards, the product was immersed in UV-curable acrylic resin (ABPE-10), without the use of solvents or vacuum, relying on its high pore volume and capillary force to achieve rapid resin penetration. After 12 hours of penetration, the xerogel changed from white to transparent ( Figure 2 ), indicating that the resin has fully penetrated. UV light (365nm) was used to cure for 15min to obtain transparent wood. Finally, by compressing the product, the wood volume fraction in the transparent wood can be controlled. In Example 1, a large transparent wood composite with a wood volume fraction of up to 50% was successfully prepared by compression treatment, demonstrating the scalability of this method ( Figure 3 The total light transmittance of the obtained transparent wood at 550nm is as high as 81.1% ( Figure 4 (a)) and has good mechanical properties, with a tensile strength of 259MPa and a Young's modulus of 29GPa ( Figure 4 (b)).
[0069] In Comparative Example 1, since the in-situ separation and cross-linking of cellulose nanofibers were not performed, the porosity and specific surface area of the product were lower than those of Example 1 ( Figure 1 (b) and Figure 1 (c)). The product was then immersed in ABPE-10 resin. Due to its low pore volume and capillary force, the resin penetrated slowly and could not completely penetrate into the cell wall, resulting in the transparent wood composite material being opaque and having low light transmittance ( Figure 5 (a) and Figure 5(b)). The compression performance and mechanical properties of the product are lower than those of Example 1, and due to the compactness of its cell wall structure, it is impossible to prepare a transparent wood composite material with a high wood volume fraction. The tensile strength and Young's modulus of the obtained composite material are lower than those of the composite material of Example 1, and the light transmittance and haze value are also unsatisfactory, indicating that the unmodified treatment has a significant effect on the properties of the transparent wood.
[0070] By comparing Example 1 and Control Example 1, it can be clearly seen that TEMPO-mediated oxidation and aluminum ion cross-linking treatment are crucial to improving the porosity, specific surface area of the wood aerogel and the optical and mechanical properties of the final transparent wood composite material.
[0071] In Control Example 2, since solvent exchange and drying treatment were not performed, the cell wall structure of the product was prone to collapse during the subsequent resin infiltration process, resulting in the inability of the resin to effectively penetrate into the cell wall. The obtained transparent wood composite material had low transparency and unsatisfactory light transmittance. The mechanical properties of the composite material obtained in Control Example 2 were also significantly affected, with tensile strength and Young's modulus both lower than those of the composite material in Example 1 ( Figure 6 (b)). In addition, due to the instability of the cell wall structure, the composite material in Control Example 2 also has poor durability in practical applications.
[0072] In the blank example, since the original wood has not been subjected to delignification, oxidation, cross-linking and solvent exchange drying treatment, its cell wall structure is tight and the resin cannot effectively penetrate into the cell wall of the wood, resulting in the extremely low transparency of the prepared composite material and the light transmittance being much lower than that of the transparent wood in Example 1 (Table 1). In addition, due to the lack of effective interface bonding, the mechanical properties of the composite material in the blank example are also far inferior to those of the composite material in Example 1 (Table 2). The composite material in the blank example exhibits lower tensile strength and Young's modulus in the tensile test, and is prone to interface peeling in practical applications, indicating that the preparation steps of the wood-based aerogel are essential for obtaining high-performance transparent wood.
[0073] The results are shown in Tables 1 and 2.
[0074] Table 1. Physical properties of Example 1, Control Example 1 and Blank Example
[0075]
[0076] Table 2. Mechanical properties of Example 1, Control Example 1 and Blank Example
[0077]
[0078] It will be apparent to those skilled in the art that the present invention is not limited to the details of the exemplary embodiments described above and that the present invention can be implemented in other specific forms without departing from the spirit or essential features of the present invention. Therefore, the embodiments should be considered exemplary and non-restrictive in all respects, and the scope of the present invention is defined by the appended claims rather than the above description, and it is intended that all changes falling within the meaning and scope of the equivalent elements of the claims be included in the present invention.
[0079] In addition, it should be understood that although the present specification is described according to implementation modes, not every implementation mode contains only one independent technical solution. This description of the specification is only for the sake of clarity. Those skilled in the art should regard the specification as a whole. The technical solutions in each embodiment may also be appropriately combined to form other implementation modes that can be understood by those skilled in the art.
Claims
1. A method for preparing transparent wood based on wood xerogel, characterized in that: The steps include: S1, delignifying the wood to obtain pretreated wood; S2, oxidizing the pretreated wood with TEMPO to obtain an intermediate product; S3, exchanging the solvent of the intermediate product and converting it into a wood xerogel, and cross-linking it with aluminum ions to obtain a precursor; S4, subjecting the precursor to a photocuring reaction with an acrylic resin to obtain a crude product; S5. Compressing the crude product to obtain a product.
2. The method for preparing transparent wood based on wood xerogel according to claim 1, characterized in that: The density of the wood is 150-400 kg / m 3 ; and cutting the wood.
3. The method for preparing transparent wood based on wood xerogel according to claim 1, characterized in that: In the step S3, the step of cross-linking the aluminum ions is to soak the wood xerogel in aluminum ion solutions of different concentrations in batches.
4. The method for preparing transparent wood based on wood xerogel according to claim 3, characterized in that: In the step S3, the concentration of the aluminum ion solution 1 is 0.1-0.5M, and the immersion time is 1-3h; the concentration of the aluminum ion solution 2 is 0.01-0.05M, and the immersion time is 10-48h.
5. The method for preparing transparent wood based on wood xerogel according to claim 1, characterized in that: In the step S4, in the photocuring reaction, the precursor is mixed with acrylic resin and photoinitiator, placed in the dark overnight, and then photocured.
6. The method for preparing transparent wood based on wood xerogel according to claim 1, characterized in that: In the step S5, the compressive strain value is 30-90%.
7. The method for preparing transparent wood based on wood xerogel according to claim 1, characterized in that: The wood is selected from balsa wood.
8. Use of the transparent wood of wood xerogel prepared by the method for preparing transparent wood of wood xerogel according to any one of claims 1 to 7 in building materials.